Real-Ambient Particulate Matter Exposure-Induced Cardiotoxicity in C57/B6 Mice - Cui, Lianhua; Shi, Limei; Li, Daochuan; Li, Xiaobo; Su, Xuan; Chen, Liping; Jiang, Qixiao; Jiang, Menghui; Luo, Jing; Ji, Andong; Chen, Chen; Wang, Jianxun; et al. (Frontiers in Pharmacology, 2020)
It is generally accepted that exposure to particulate matter (PM) increases the risk of cardiovascular-related morbidity and mortality, while the exact mechanism has yet to be elucidated. Oxidative stress plays a potentially important role in the mechanism of toxicity, with Nrf2 serves as a major antioxidant gene. In the current study, a Nrf2 knockout mouse model was used in combination with an individual ventilated cage (IVC)-based real-ambient PM exposure system to assess the potential cardiotoxicity induced by real-ambient PM exposure and the potential role of Nrf2 and related signaling in this endpoint. After 6 or 11 weeks exposure to PM, ICP-mass spectrometry was used to assess the heavy metal depositions in the heart tissue following PM exposure. Functional and morphological changes in the hearts were investigated with echocardiography and histopathology, and oxidative stress levels were assessed with the serum malondialdehyde content assay. In the further mechanistic study, RNA-seq technique was utilized to assess the gene transcription status in the hearts of C57/B6 mice exposed to PM, with or without Nrf2 knockout. The expression levels of genes of interest were then further investigated with quantitative real-time PCR and western blotting.The results indicated that PM exposure resulted in significant elevation of sodium, potassium, selenium and ferrum levels in mouse heart tissue. Meanwhile, significantly altered heart function and morphology were observed. Interestingly, Nrf2 knockout led to abolishment of PM-induced effects in several functional parameters, but not the morphological changes. Meanwhile, elevated malondialdehyde contents were observed in Nrf2 knockout animals. RNA-seq results revealed thousands of genes altered by PM exposure and/or Nrf2 knockout, affecting several pathways, such as MAPK, phagosome, calcium signaling and JAK-STAT. In subsequent molecular studies, enhanced nuclear translocation of Nrf2 was also observed following PM exposure, while MAPK signaling pathway along with related JAK-STAT and TGF-β1 pathway genes, such as p38MAPK, AKT, TAK1, JAK1, STAT3, GRB2, TGFb1 and SMAD2 were confirmed to be affected by PM exposure and/or Nrf2 knockout. The data suggested that PM may induce cardiotoxicity in C57/B6 mice, in which Nrf2 plays both protective and detrimental roles, involving cardiac-related pathways such as MAPK, JAK-STAT and TGF-β1.